Techniques of presence. Beyond presence and its crisis - Capozzi, Simone (Campos - Revista de Antropologia, 2024)
In the following pages, I will outline some meanings of the concept of presence in the work of Ernesto de Martino, starting from the Il mondo magico. Prolegomeni ad una storia del magismo up to the last writings of La fine del mondo. Contributo all’analisi delle apocalissi culturali and Scritti filosofici, collected by Roberto Pàstina. The concept of “presence” initially coincides with the Kantian synthetic unity of apperception and its crisis, but in his later writings, it is replaced by the concept of presentification. My aim is to highlight how de Martino’s latest writings open up to the themes of the construction of “presence”. The process of presentification emerges as the result of the relationship of use between the body and certain techniques. Therefore, I will analyze the three contiguous concepts of use, habit and domestication.